Real-World Analysis Evaluating Treatment Eligibility and Outcomes in Patients With AML Receiving Intensive Chemotherapy: Insights From an Underrepresented Population - Hasmukh Jain; Thomas Eipe; Alok Shetty; Lingaraj Nayak; Bhausaheb Pandurang Bagal; Neha Sharma; Akash Pawar; Manju Sengar (JCO Global Oncology)
PURPOSEOver the past decade, there have been significant advancements in the treatment of AML. However, similar progress has not been observed in India, with induction mortality rates surpassing those in high-income countries. Our patient population also differs significantly from those in clinical trials, with about 50% ineligible for intensive chemotherapy. Yet, because of limited access to newer therapies and high costs, most of these patients receive intensive therapy.PATIENTS AND METHODSIn this study, we retrospectively classified patients who received intensive induction into fit and unfit groups on the basis of landmark trial criteria. Data were extracted from the Indian Acute Leukemia Research Database, a prospective registry maintained under the Hematology Cancer Consortium. The primary objective was induction mortality.RESULTSWe analyzed 385 patients with AML treated between 2017 and 2019. The median age at diagnosis was 33 years (range, 15-61). Induction mortality was reported at 6.1% in the fit cohort and 20.2% in the unfit cohort (odds ratio, 3.91 [1.97-7.74]; P < .0001). Factors such as increased age, poor performance status, baseline infection, and low albumin were associated with a poor prognosis for early death. After a median follow-up of 19.2 months, the 2-year overall survival in the overall, fit, and unfit cohorts was 62.7%, 67%, and 58.1%, respectively.CONCLUSIONOur findings highlight the baseline characteristics of our patient population and their impact on the outcomes of induction therapy. Unfit patients who received intensive chemotherapy had higher induction mortality and lower overall survival.